2000
DOI: 10.1007/pl00013677
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mobility of sorbitol and maltitol: A ^13C NMR and molecular dynamics approach

Abstract: Molecular mobility in two similar organic glass formers, namely sorbitol and maltitol, is studied in order to understand their difference in the cross-over between α and β relaxations, far above their respective glass transition temperatures. In this goal, the individual mobility of each carbon atom of the 6 carbon chain present both in sorbitol and maltitol is studied by means of 13 C nuclear magnetic resonance and molecular dynamics simulations. Both techniques imply that the mobility of carbons located at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…More recently, Sixou et al . have shown that the C-1–H bond vectors in sorbitol reorient faster than the C-4–H bond vectors at T = 400 K, in agreement with 13 C NMR measurements 13,14. These workers concluded that the main contribution to the C-1–H reorientation is associated with local conformational transitions.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…More recently, Sixou et al . have shown that the C-1–H bond vectors in sorbitol reorient faster than the C-4–H bond vectors at T = 400 K, in agreement with 13 C NMR measurements 13,14. These workers concluded that the main contribution to the C-1–H reorientation is associated with local conformational transitions.…”
Section: Introductionsupporting
confidence: 63%
“…Several types of experimental data exist for comparison purposes. These include crystal structures for sorbitol,1012,17 13 C NMR relaxation times for pure (neat) liquid sorbitol,13,14 and additional 1 C NMR data concerning the populations of conformers in aqueous solution 1820…”
Section: Introductionmentioning
confidence: 99%
“…116 The molecular dynamics in sorbitol and maltitol were compared using 13 C NMR in order to explain the differences in the crossover between the a-and the b-relaxations above their respective T g values. 117 Studies correlating chemical stability with local mobility have been carried out by Yoshioka et al 8,9,97 as described earlier.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…This seems to be supported by the existence of T cross above T g , or the Arrhenius behavior even above T g , for supercooled liquids (see, e.g., Refs. [91][92][93][94][95][96][97]) and also for plastic crystals [98]. However, the data analysis in the crossover region is not easy and further studies are necessary to settle this problem.…”
Section: Our Assignmentmentioning
confidence: 99%